1988
DOI: 10.1002/dev.420210304
|View full text |Cite
|
Sign up to set email alerts
|

Physical stimulation reduces the body temperature of infant rats

Abstract: Physical stimulation of rat pups, of the type normally received from the mother, has been shown to regulate several behavioral and physiological systems in the young. The present paper describes a possible role of physical stimulation in an additional physiological system; the thermoregulatory system. Within a thermoneutral environment, physical stimulation produces a decrease in rectal temperature (Expt. 1). Even in an environment of increasing temperature, similar to that pups experience when in contact with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

1988
1988
2012
2012

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 47 publications
0
15
0
Order By: Relevance
“…The present findings suggest that an increased frequency of pup LG typical of High-LG mothers associates with an increased conversion of the T4 precursor to the more active T3 in BAT (figure 2c). Interestingly, pup LG produces a modest but physiologically relevant decrease in pup body temperature [38], which commonly associates with increased sympathetic activity. Sympathetic activation of BAT stimulates the conversion of T4 to T3 [39].…”
Section: Discussionmentioning
confidence: 99%
“…The present findings suggest that an increased frequency of pup LG typical of High-LG mothers associates with an increased conversion of the T4 precursor to the more active T3 in BAT (figure 2c). Interestingly, pup LG produces a modest but physiologically relevant decrease in pup body temperature [38], which commonly associates with increased sympathetic activity. Sympathetic activation of BAT stimulates the conversion of T4 to T3 [39].…”
Section: Discussionmentioning
confidence: 99%
“…We therefore paired the odor with high humidity, which does not evoke an increase in respiration, and tested for a behavioral preference and an enhanced glomerular response to the odor on day 19. We found that pups acquired a preference and an enhanced glomerular response to the conditioned odor without an increase in respiration during training (Sullivan et al, 1988b). Therefore, differential respiration of the odor during early olfactory preference conditioning is not critical for development of the altered neurobehavioral response (Do, Sullivan, and Leon, 1988).…”
Section: Role Of Stimulus Availabilitymentioning
confidence: 97%
“…Despite this relative immaturity, however, these pups exhibit a fair degree of thermoregulatory competence within the context of their normal environment-the litter situation. For example, pups exhibit thermotaxis, seeking out both the warm dam and the litter (Sullivan et al, 1988). The objective of the present investigation was to understand better some of the possible confounding factors caused by direct dosing of pups during the pre-weaning developmental period.…”
Section: Discussionmentioning
confidence: 99%
“…Any extended disruption of the social relationship of dams and pups as a result of dosing and/or direct effects caused by the administered substance would be expected to be associated with a fall in the body temperatures of pups. Sullivan et al (1988) have shown that the mere physical stimulation of rat pups (stroke and shake, of the type normally received from the mother) affects the regulation of several behavioural and physiological systems of the young. Especially for neonatal mice-an altricial species-the thermoregulatory status is exceptionally dynamic and changes rapidly and profoundly during postnatal ontogenesis from poikilothermic to homeothermic.…”
Section: Discussionmentioning
confidence: 99%